Peran Kepala Sekolah Dalam Pembelajaran Berbasis Entrepeneurship (Studi Deskriftif Di SMKN 1 NGAWI) - Lamijan, Lamijan (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this research is to be able to understand and analyze the role of school principals in the entrepreneurship-based school curriculum including in curriculum planning, implementation of learning and monitoring evaluation as well as designing follow-up actions as a continuation of the planned program. This research is based on the existence of entrepreneurship learning which has its difficulties for teachers and principals. The design of this study uses quantitative descriptive and data collection is in the form of observation, interview, and documentation. The data analysis used a qualitative descriptive which begins with the data collection stage and ends with drawing conclusion through in-depth study and description based on the research objectives. The results of the study describe how important the responsibility and role of principal is in guiding all existing staff when implementing a program, not only when assisting in curriculum development but also implementation to produce follow-up as a provision given to students with more dominant skills that will be a benchmark for learning success.